Autoamputation of Genitalia in Bipolar Patient - Vinod Sharma; Aditi Sharma (Case Reports in Psychiatry)
According to literature, genital self-mutilation (GSM) is more commonly associated with psychosis as compared with self-mutilation as a whole. There have been many case reports of GSM in psychotic disorders. We describe herein a case of a Caucasian, employed, and married male suffering from bipolar disorder type II with history of self-mutilating behavior, who amputated his penis during symptom-free phase of his illness. Several features are reflected as risky elements for genital self-mutilation, for example, homosexual and transsexual tendencies, abandonment of the male genitals, lack of competent male for identification during childhood, feeling of guilt for sexual offences, and self-injuries in anamnesis. This report will highlight various factors responsible for self-mutilation in nonpsychotic and nondelusional person.